PERANCANGAN SISTEM MEKATRONIKA PADA MESIN PEMOTONG RUMPUT MENGGUNAKAN HYBRID ENERGY - Aljufri Aljufri; Abdul Rahman; Reza Putra (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2023)
This design aims to apply mechatronics technology to a lawn mower. The test includes energy source, transmission capability and comparison of energy consumption with conventional engines This lawn mower design uses a battery with a voltage of 12 volts with a current of 7.2 Ah. The control system is with a frequency of 315 Mhz. Actuators consist of three namely, cutting motor, transmission drive motor and servo motor. Charging the battery uses a hybrid system, namely a solar cell with a capacity of 10 wp and an electric charger of 72 Watts. The engine can operate depending on the power used with a vulnerable time of 50 minutes to 75 minutes per charge. The fastest time when testing at a grass height of 20 mm with a work duration of 6 minutes 15 seconds while the longest time at a grass height of 60 mm for 11 minutes 30 seconds. The charging time of the battery using the longest solar cell on the fourth day for 11 hours and 43 minutes, while the fastest time on the fifth day is during for 6 hours and 42 minutes. For charging using charging a charging time of 1 hour 12 minutes. This machine is more efficient up to 59,000 per month with the same parameters as conventional machines